Patterns of Statin Use in Older Medicare Beneficiaries With Traumatic Brain Injury. (August 2017) - Khokhar, Bilal; Simoni-Wastila, Linda; Slejko, Julia F.; Perfetto, Eleanor; Zhan, Min; Smith, Gordon S.
Background: In addition to lowering lipids, statins also may be beneficial for older adults sustaining a traumatic brain injury (TBI), as statin use prior to and following trauma may decrease mortality following injury. However, despite statins' potential to reduce mortality, there is limited research regarding statin use among older adults.Objective: To characterize and investigate factors associated with statin use among older adults with TBI.Methods: A retrospective drug utilization study was used to characterize statin use among Medicare beneficiaries 65 and older hospitalized with a TBI during 2006 to 2010 and with continuous Medicare Parts A, B, and D coverage 6 months prior and 12 months following TBI. Logistic regression was used to investigate the factors associated with statin use. The exposure of interest was statin use prior to and following TBI.Results: Of the 75 698 beneficiaries included in the study, 37 874 ( 50%) of beneficiaries used a statin at least once during the study period. The most common statin used was simvastatin, while fluvastatin was the least used statin. Statin users were more likely to have cardiovascular diseases when compared to nonusers. Hyperlipidemia was a major factor associated with statin use and had the greatest impact on statin use compared to nonuse (odds ratio = 9.54; 95% confidence interval = 9.07, 10.03).Conclusions: This national sample of older adults with TBI suggests that statins are commonly used. Future studies must next examine the impact of statin use on mortality and secondary injury in order to shape pharmacological therapy guidelines following TBI.